Enhancing structural support of the dermal microenvironment activates fibroblasts, endothelial cells and keratinocytes in aged human skin in vivo - Quan, Taihao (2012)
The dermal extracellular matrix (ECM) provides strength and resiliency to skin. The ECM consists mostly of type I collagen fibrils, which are produced by fibroblasts. Binding of fibroblasts to collagen fibrils generates mechanical forces, which regulate cellular morphology and function. With aging, collagen fragmentation reduces fibroblast-ECM binding and mechanical forces, resulting in fibroblast shrinkage and reduced function including collagen production. Here, we report that these age-related alterations are largely reversed by enhancing structural support of the ECM. Injection of dermal filler, cross-linked hyaluronic acid, into the skin of persons over seventy years-old stimulates fibroblasts to produce type I collagen. This stimulation is associated with localized increased of mechanical forces, indicated by fibroblast elongation/spreading, and mediated by up-regulation of type II TGF-β receptor and connective tissue growth factor. Interestingly, enhanced mechanical support of the ECM also stimulates fibroblast proliferation, expands vasculature, and increases epidermal thickness. Consistent with our observations in human skin, injection of filler into dermal equivalent cultures causes elongation of fibroblasts, coupled with type I collagen synthesis, which is dependent on the TGF-β signaling pathway. Thus, fibroblasts in aged human skin retain their capacity for functional activation, which is restored by enhancing structural support of the ECM.